Povratnička priča i književni uspjeh egzilanta - Lovrenčić, Željka (Array, 2008)
Writer and publicist Drago Šaravanja (1940) had the typical biography of an exile writer on the road from Europe to Australia and back to the homeland. Along with his work as a writer Šaravanja had a successful business career in Australia and can be proud of the no less important fact that he, as a 19-year-old exile from the homeland, by hard work and parallel schooling managed to earn his family an enviable status in Australia. Šaravanja's success in Australia and Croatia is continued by his highly educated sons (one in economics, the other in the medical sciences, one in Australia, the other an immigrant to Croatia – his father's land). Returnee Šaravanja has these days released an interesting novel with autobiographic elements called Na drugoj strani vremena (On the Other Side of Time). Šaravanja's already published works include: the collection of poetry Svaka rijeka svome moru teče (Every River Flows to Its Sea) (Sydney, 1993); the epic Hrvatska sloboda (Croatian Liberty) (Sydney, 1994); the historical monograph Hrvati sa Snježnih planina (The Snowy and Croatians) (Sydney, 1999) – also found at the Mitchell's State Library in Sydney. There are the anthologies: Hrvatska iseljenička lirika (Croatian Emigrant Lyricism) (1974) edited by Friar Lucijan Kordić; Hercegovina (2002) edited by Vjekoslav Boban; the bilingual collection of short stories by Croatian writers in Australia Zrcala u sjeni (Mirrors in the Shadow); Writers' Mosaic (1992, 1993, 1996), a collection of short stories by Australian writers; the novel Idemo kući (We're Going Home), and now the novel Na drugoj strani vremena. Šaravanja's latest novel is a convincing saga of a life that took place in post-war Yugoslavia, a saga of a young man that, like many other Croatians, had to leave his country because he was threatened in it. Drago Šaravanja returned to Croatia in February of 2001 after having lived abroad for 42 years.